PENGARUH KUALITAS PELAYANAN BERBASIS SYARIAH TERHADAP LOYALITAS PASIEN DI APOTEK KARUNIA SEHAT BARU UNGARAN - Naniek Widyaningrum; Agustina Sawitri; Nurita Indriani (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2023)
Patient loyalty is one of the things that is important for the ongoing pharmacy business. And one of the things to increase patient loyalty is to provide Islamic-based services. And in this study aims to determine the benefits of Islamic principled services at the karunia sehat baru Pharmacy in Ungaran, to determine the relationship between Islamic principled services and patient loyalty at the karunia sehat baru Pharmacy in Ungaran, Services with sharia principles have four characters, namely Rabbaniyyah, Akhlaqiyyah, Waqi'iyah and Insaniyyah. Data collection techniques by distributing questionnaires to patients at the pharmacy. The results of this study indicate that sharia-based pharmaceutical services consisting of Rabbaniyyah, Akhlaqiyyah, Waqi'iyah and Insaniyyah have a positive effect on patient loyalty. And Rabbaniyyah and Akhlaqiyyah have a significant influence on patient loyalty at the karunia sehat baru pharmacy in Ungaran.